The Effect of Decis Insecticide on the Mortality and Gill Histological Structure of the Red Indigo "Cangkringan local strain" - Wahyuni Wulandari; Sukiya .; Suhandoyo . (Jurnal Sain Veteriner, 2013)
Abstract This study was aimed to determine the effects of Decis insecticide on the mortality, its safe level concentration against mortality, and the cytotoxic effects in the gills of the red tilapia strains of "localCangkringan" collected from Fish Seed Center, Cangkringan, Sleman, Yogyakarta. Eight hundreds fishweighing 0.5-1.0 g and 2-12 weeks old each were collected randomly and divided into 5 groups with Decis insecticide concentration of 0.27 ppm, 0.81 ppm, 1.00 ppm, 1.35 ppm, 2.4 ppm, respectively and a control group based on preliminary testing. Each treatment comprised three replicates, 10 replicates of each test fish. The observations of fish mortality to the test were done every hour - 24, for 96 hours of treatment, whereas mortality at safe levels test done every 4 weeks for 2 months of treatment. Data were analyzed using probit analysis to determine LC50 and LC50-96 hours-48 hours. The assay of 10% safe levels of LC50-48 hours is 0.13 ppm. Twofactorial analysis of variance was to determine the effect of concentration and duration of exposure to the Decis insecticide test fish mortality. Independent samples of T test analysis was applied to determine the effect of safe levels. The descriptive and qualitative analysis was done to determine the pathologic lesions on fish gills due to the cytotoxicity of Decis insecticide. Results of the present study showed that the variation of concentrations of Decis insecticide has significant effect on fish mortality (p <0,01). Decis insecticide concentration used for the LD50(96 hours)  was 1.21 ppm that was the highly toxic class to Nila. It caused severe cytotoxic efects to the gills  indicated by the presence of gills necrosis, hypertrophy, hyperplasia dan diffuse hemorrhages. The safety levelsof Decis concentration still caused mild histopathological lesions, such as focal to multifocal hemorrhages and congestion in the gills